Rehabilitation in Heart transplant with Covid-19 in UCI-Case report - Maria Loureiro; João Duarte; Marco China; Maria Manuela Martins; Gonçalo Coutinho; André Novo (Instituto Politécnico de Viseu, 2023)
Introduction: Solid-organ transplant patients have a high risk of severe infection related to COVID-19 disease. In heart transplanted patients the impact of this infection remains unknown, as well as importance of rehabilitation, on recovery process. Objective: To describe intervention of rehabilitation nurse in a case of a heart transplanted person infected with COVID-19 in UCI. Methods: Case report follow CARE guidelines. This case represents a 60-year-old man, a heart transplant recipient, who presented with a 5-day history of cough, fever, and activity intolerance, who required hospitalization in intensive care. Rehabilitation nursing intervention in respiratory and functional functions was due 2 times a day, during 30-45minutes, adapted to the evolution of the person. Results: This case supports the possibility and impact of rehabilitation nursing intervention, in the multidisciplinary team, on the improvement of the person, either through the improvement/resolution of the rehabilitation nursing diagnosis status or on the clinical improvement of the person. Demonstrates the possibility of prescribing early mobilization interventions, breathing exercises in the context of the transplanted person with severe covid disease, admitted to the ICU, using different techniques. Conclusion: Rehabilitation Nursing interventions, in this case, translated into an improvement in the respiratory and functional function of a heart transplant patient infected with COVID-19during UCI care.